Distribution serovar and risk factors on the incidence of canine Leptospirosis after flood in Jakarta, Indonesia - Ambar, Retnowati; Agustin, Indrawati; Hadi, Upik Kesumawati; Safika,; M Noor, Susan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Leptospirosis is a zoonosis, which has become a serious problem, especially in areas with high rainfall. Massive leptospirosis occurs after heavy rains or floods. This study aims to analyze the types and distribution of leptospira bacteria serovars and risk factors for leptospirosis in post-flood dogs. The research was conducted from January to March 2020 at the Ragunan Animal Hospital and independent clinics in Jakarta, Bekasi, Depok and South Tangerang. This study used a cross-sectional study of serum samples from 24 dogs suspected of leptospirosis. Diagnostic techniques are based on questionnaires and clinical symptom evaluation, physical examination and biochemical analysis, serum and hematology, and the Microscopic Agglutination Test (MAT) test. The sample criteria were dogs with leukocytosis, thrombocytopenia, azotemia with Blood Urea Nitrogen (BUN) and high keratin. The sample then tested the MAT. Measurement of risk factors in the form of variable questionnaires with laboratory test results using the Chi-square test. Leptospira serovars were identified as bataviae (9 samples), icterohaemorrhagiae (6 samples), tarassovi (4 samples) and javanica (2 samples). The distribution of leptopsira serovars in the study area is quite diverse. Risk factors that increase the incidence of leptospirosis in dogs are the maintenance system (OR 17.50), history of contact with rats (OR 9.625), flood-affected areas (OR 3.50) and drinking water sources (OR 1.643). Floods can be a medium for transmitting leptospira bacteria to dogs. Risk factors such as rearing systems, poor sanitation and a history of contact with rats can increase the incidence of leptospirosis in dogs in areas with high rain intensity. The role of dog owners is needed in preventing the incidence of leptospirosis in dogs.